LncRNA NKILA suppresses TGF‐β‐induced epithelial–mesenchymal transition by blocking NF‐κB signaling in breast cancer. Issue 9 (7th August 2018) - Wu, Wei; Chen, Fei; Cui, Xiuying; Yang, Limei; Chen, Jianing; Zhao, Jinghua; Huang, Di; Liu, Jiang; Yang, Linbin; Zeng, Jiayi; Zeng, Zhiqing; Pan, Yunbao; et al.
Abstract : TGF‐β plays a central role in mediating epithelial–mesenchymal transition (EMT) by activating the Smad pathway. In addition, accumulating evidence suggests that TGF‐β‐induced EMT is NF‐κB‐dependent in various cancer types. However, it is largely unclear if NF‐κB mediates TGF‐β‐induced EMT in breast cancer, and if this mediation occurs, the regulatory mechanisms are unknown. In our study, we found that TGF‐β activates the NF‐κB pathway. Inhibition of NF‐κB signaling markedly abrogates TGF‐β‐induced EMT. By studying the regulatory mechanism of TGF‐β‐induced NF‐κB signaling, we found that lncRNA NKILA was upregulated by TGF‐β and was essential for the negative feedback regulation of the NF‐κB pathway. Accordingly, overexpression of NKILA significantly reduced TGF‐β‐induced tumor metastasis in vivo . Consistent with the results from mice, the expression of NKILA was negatively correlated with EMT phenotypes in clinical breast cancer samples. Collectively, our study indicated that the NKILA‐mediated negative feedback affects TGF‐β‐induced NF‐κB activation and that NKILA may be a therapeutic molecule in breast cancer metastasis via inhibition of EMT. Abstract : What's new? TGF‐β plays an important role in inducing epithelial‐mesenchymal transition (EMT), which is closely associated with distal metastasis of breast cancer. TGF‐β‐induced EMT has been shown to be NF‐κB‐dependent in various cancer types, but whether, and how, NF‐κB mediates TGF‐β‐induced EMT in breast cancer remains unclear. Here, the authors report that NF‐κB mediates TGF‐β‐induced EMT in breast cancer. NF‐κB activation and subsequent EMT induced by TGF‐β are finely tuned by the negative feedback regulation of lncRNA NKILA. The data extend the understanding of NF‐κB feedback regulatory mechanisms and suggest that NKILA may be an attractive therapeutic molecule for targeting tumor metastasis.